2020
DOI: 10.1007/s40820-019-0362-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Theranostic Properties of Titanium Dioxide for Nanomedicine

Abstract: HIGHLIGHTS • Multifunctional TiO 2 nanostructures hold promise for advancing a wide range of biomedical applications due to a feasible integration of distinct theranostic features. • Fabrication and post-fabrication strategies implemented to generate multifunctional TiO 2 nanostructures for a broad range of biomedical applications are briefly outlined. The opportunities and challenges of TiO 2 nanomaterials are highlighted in order to open the possibility of clinical translation. ABSTRACT Titanium dioxide (TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 222 publications
0
23
0
Order By: Relevance
“…In this case, the carboxylic group on the surface of AuNPs was then substituted with N-hydroxysuccinimide (NHS) by using 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC) to readily react with the primary amines (NH 2 ) of the antibodies to form a covalent amide bond. 19 The conjugated AuNPs were characterized through the use of dynamic light scattering (DLS), spectrophotometer, and transmission electron microscopy (TEM) (Figure 1). Taking advantage of plasmonic resonance of plasmonic NPs that are highly sensitive to surface modifications, 16,20 the absorbance spectrum of the antibody functionalized AuNPs (Ab-PEG 5kDa -AuNPs), which showed a plasmon peak at 574 nm as well as a resonance shift (∼6 nm), was found broader for Ab-PEG 5kDa -AuNPs compared to PEGylated AuNPs (plasmon peak at 568 nm) because of the presence of antibodies on the surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this case, the carboxylic group on the surface of AuNPs was then substituted with N-hydroxysuccinimide (NHS) by using 1-ethyl-3-(3-(dimethylamino)propyl)carbodiimide (EDC) to readily react with the primary amines (NH 2 ) of the antibodies to form a covalent amide bond. 19 The conjugated AuNPs were characterized through the use of dynamic light scattering (DLS), spectrophotometer, and transmission electron microscopy (TEM) (Figure 1). Taking advantage of plasmonic resonance of plasmonic NPs that are highly sensitive to surface modifications, 16,20 the absorbance spectrum of the antibody functionalized AuNPs (Ab-PEG 5kDa -AuNPs), which showed a plasmon peak at 574 nm as well as a resonance shift (∼6 nm), was found broader for Ab-PEG 5kDa -AuNPs compared to PEGylated AuNPs (plasmon peak at 568 nm) because of the presence of antibodies on the surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In general, SLIPS consists of three parts: i) a structured rough substrate, ii) an appropriate low surface energy coating, and iii) a low‐surface‐tension fluid frequently called lubricant. [ 14 ] So far, a variety of materials such as metals, [ 10g,12,13c,15 ] polymers, [ 10c,16 ] fabrics, [ 17 ] ceramics, [ 10h,18 ] to name a few, have been structured to fit the nanometer‐scale roughness requirement. [ 19 ] However, only a few approaches have been adopted to reduce the surface energy of these substrates, utilizing mostly hydrocarbon‐ or fluorinated chains with silane‐ [ 10h,18a,20 ] or phosphate‐based functional binding groups.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing concentration of singlet oxygen and hydroxyl radicals, 4T1 cells would be gradually damaged and lead to cell senescence and death due to oxidative damaging effects [ 11 , 42 , 43 ]. Due to the enhanced permeability and retention (EPR) effect, C-doped TiO 2 preferentially accumulates in tumor cells eliciting efficient ROS generation [ 44 ] and further increasing the effectiveness of the SDT treatment. It was also revealed that the suppression of the tumor is due to the elevated level of ROS which results in both direct tumor cell death and blood vessel stasis.…”
Section: Discussionmentioning
confidence: 99%